2017
DOI: 10.1136/esmoopen-2017-000222
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab as second-line therapy in non-small cell lung cancer in northern Norway: budget impact and expected gain—a model-based analysis

Abstract: BackgroundPembrolizumab is a new drug approved in several countries for second-line therapy in non-small cell lung cancer (NSCLC) being programmed cell death ligand (PD-L1) positive. This drug has a high cost, and the cost-effectiveness ratio has been debated.Patients and methodsThe budget impact to the Northern Norwegian Regional Health Authority trust of implementing pembrolizumab in second-line therapy in patients with PD-L1-positive NSCLC was calculated. A model was developed employing data from the Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Therefore, indirect costs might be reduced through a lower burden on informal caregivers and return to work for some patients. Our results are consistent with the study by NORUM et al [11], who estimated the annual budget impact in Norway to be €5 million for 105 NSCLC patients treated with pembrolizumab as a second-line therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, indirect costs might be reduced through a lower burden on informal caregivers and return to work for some patients. Our results are consistent with the study by NORUM et al [11], who estimated the annual budget impact in Norway to be €5 million for 105 NSCLC patients treated with pembrolizumab as a second-line therapy.…”
Section: Discussionsupporting
confidence: 93%
“…However, these new agents are extremely expensive [7][8][9][10], and nationwide data on budget impact are scarce. We identified only one study that showed 105 NSCLC patients per year would be eligible for anti-PD-1 treatment in Norway, with an annual budget impact amounting to €5 million [11]. However, only 2500 new NSCLC cases are diagnosed each year in Norway and this study was limited to pembrolizumab as second-line therapy for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 35 publications remaining, 15 were further eliminated; eight were unpublished abstracts and five were review articles. Two publications were ultimately removed owing to non-modeling and/or non-comparative designs that evaluated cost but not specifically CE [ 23 , 24 ]. Thus, 20 original investigations were found to have sufficient focus and relevance to be incorporated into the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…During the last years, new costly drugs have been introduced for the treatment of lung cancer. 8 Examples of inhibitory signalling agents approved by the Food and Drug Administration include antibodies targeting cytotoxic T-lymphocyte-associated protein 4 and programmed death 1 (PD-1)/PD-ligand 1 (L1) receptors. 9 Especially, PD-1/PD-L1 blockage therapy has shown activity in lung cancer.…”
Section: Introductionmentioning
confidence: 99%